ANALISIS TINGKAT KEPUASAN PENUMPANG TERHADAP KUALITAS PELAYANAN DI BANDAR UDARA INTERNASIONAL KUALANAMU - Muhammad Dhio Darus; Kasyful Mahalli (Departemen Ekonomi Pembangunan USU, 2015)
This study is to determine the level of passenger satisfaction with service quality in Kualanamu International Airport and to reveals the effort / strategy led by PT. Angkasa Pura II in achieving World Class Airport in Kualanamu International Airport. The method of data collection is done by questionnaires and direct interviews with informants. Analyze data using Customer Satisfaction Index (CSI) to determine the satisfaction of passengers. The results shows that the Customer Satisfaction Index (CSI) at the level of to 73.6%, which means the value is in the category are enough satisfied. This shows that passengers satisfied with the performance and service given by PT. Angkasa Pura II. PT Angkasa Pura II has done some acceleration of infrastructure develop and conduct business strategy and synergy with related units. With the infrastructure and other developments are expected to achieve World Class Airport at least in terms of service.Keywords : Passenger Satisfaction, Quality of Service, Customer SatisfactionIndex (CSI), World Class Airport